IMPLEMENTATION OF BIOMETRIC TECHNOLOGY TO IMPROVE ACCESS AND SECURITY OF DIGITAL FINANCIAL SERVICES - Gunawan Widjaja (Adisam Publisher, 2025)
The development of digital financial services brings new challenges related to data security and user identity protection. Biometric technologies, such as fingerprint and facial recognition, offer more secure and practical authentication solutions than conventional methods such as PINs or passwords. This study aims to examine the effectiveness of biometric implementation in enhancing the security and accessibility of digital financial services through a literature review of various scientific sources and recent industry reports. The results of the study indicate that biometrics significantly reduces the risk of identity theft and illegal access, as well as speeds up the user verification process. In addition, this technology also supports financial inclusion by facilitating access for previously underserved communities. However, challenges related to data privacy, implementation costs, and infrastructure readiness remain major concerns. Therefore, collaboration between financial institutions, regulators, and technology providers is essential to ensure the safe, efficient, and inclusive implementation of biometrics in the digital financial ecosystem.